Psycho Religi Jamaah Haji Lansia Nusantara (Perspektif Bimbingan Konseling Islam) sebagai Upaya Pengembangan Program Studi BKI (Jurusan Bimbingan dan Konseling Islam, 2019)
This study discusses the psycho religion of elderly pilgrims in the perspective of counseling guidance services. This research aims to develop the Islamic Guidance and Counseling study program in the religious psycho of the elderly pilgrims of the archipelago. This type of research uses qualitative research methods. the conclusion can be drawn that First, the inner atmosphere of the archipelago elderly pilgrimage at the time ahead, the process, and post-hajj can be described as they are very happy, happy, and grateful. Second, the factors that encourage to welcome God's call as dhuyufur rohman in haromain are (1) as a form of hambba obedience to his rabb (2) Support from children. (3) The community of recitation worshipers. (4) The reward (reward) promised by Allah through the Messenger of Allah that those who hajj mabrur repay is heaven. Third, the spiritual experience experienced by the elderly pilgrimage while performing the hajj in Haromain.